PENGEMBANGAN PELAYANAN PENYAKIT ASAM URAT PADA POSBINDU PENYAKIT TIDAK MENULAR - Zahtamal, Zahtamal; Nazriati, Elda; Restila, Ridha (MAJU : Indonesian Journal of Community Empowerment, 2024)
Many people in Buluhcina village, Kampar district, experience gout. The causes include the lack of ideal community behavior in preventing and managing disease. The aim of this empowerment activity is to optimize the role of the non-communicable disease (NCD’s) Posbindu and increase community understanding about the prevention and management of gout. The targets of the community empowerment activities that have been carried out are Posbindu NCD’s cadres and the community in Buluhcina Village, Kampar Regency. The empowerment method that has been carried out is education and community empowerment. Based on the evaluation results obtained, the activities have been able to help provide health human resources and facilities that can help manage gout in the community, especially during the Covid-19 pandemic. This activity has also been able to increase community knowledge and practice in preventing and managing gout.